Neurofeedback as placebo: a case of unintentional deception? - Kalokairinou, Louiza (Journal of medical ethics, 2022)
The use of placebo in clinical practice has been the topic of extensive debate in the bioethics literature, with much scholarship focusing on concerns regarding deception. While considerations of placebo without deception have largely centred on open-label placebo, this paper considers a different kind of ethical quandary regarding placebo without an intent to deceive—one where the provider believes a treatment is effective due to a direct physiological mechanism, even though that belief may not be supported by rigorous scientific evidence. This is often the case with complementary and alternative medicine (CAM) techniques and also with some mainstream therapies that have not proven to be better than sham. Using one such CAM technique as a case study—electroencephalography (EEG) neurofeedback for attention-deficit/hyperactivity disorder (ADHD)—this paper explores the ethics of providing therapies that may have some beneficial effect, although one that is likely due to placebo effect. First, we provide background on EEG neurofeedback for ADHD and its evidence base, showing how it has proven to be equivalent to—but not better than—sham neurofeedback. Subsequently, we explore whether offering therapies that are claimed to work via specific physical pathways, but may actually work due to the placebo effect, constitute deception. We suggest that this practice may constitute unintentional deception regarding mechanism of action. Ultimately, we argue that providers have increased information provision obligations when offering treatments that diverge from standard of care and we make recommendations for mitigating unintentional deception.